Stuck in the middle: Generation Xers lived experiences in the workforce while navigating between Baby Boomers and Millennials, and perceived impact on their job satisfaction - Dickson, Suzanne Armatas, author; Lynham, Susan A., advisor; Peila-Shuster, Jackie, committee member; Steger, Michael, committee member; Wallner, Barbara, committee member (Colorado State University. Libraries, 2015)
Generation Xers are defined as those individuals born between the years of 1965-1980, and represent between 46-49 Million in the U.S. population, and are considered a much smaller cohort than Boomers (80 Million) and Millennials (78 Million). Gen Xers argue that they are overshadowed by the notable influence of the Boomers and a perceived anticipation of the Millennials to become "the next great generation" in the workforce and as such, describe themselves as "stuck in the middle" while waiting for Boomers to retire so they may advance in their careers. However, pronounced demographic trends may have exacerbated Gen Xers' perceptions of neglect and being stuck in the middle. These demographic trends include Boomers continuing to work and Millennials entering the workforce and bringing with them vastly different work preferences, values and expectations than the proceeding generational cohorts. These two dimensions --Boomers continuing to work, and Millennials entering and beginning to influence the workforce--suggest a potentially enigmatic challenge for the smaller but still relevant cohort of Gen Xers with the potential impact on Gen Xers being relatively unknown. This exploratory study was to examine the unique workforce experiences of Gen Xers as it related to being stuck between the Baby Boomers and Millennials and thereby, gain understanding of the perceived impact to their job satisfaction. To describe, understand and find meaning in the participants co-constructed findings, a hermeneutic phenomenology methodology was utilized that was grounded in a constructivist paradigm. The findings from this study represent the individual, shared and co-constructions of six participants which resulted in twelve global themes. The twelve themes include: 1: "Stuck in the middle" is experienced and expressed differently by Gen Xers; 2: Gen Xers have anxiety about their professional future; 3: There are challenges unique to Gen Xers; 4: Gen Xers have perceptions about themselves and their work role; 5: There are generational similarities and differences; 6: Unique work culture impacts generational issues; 7: There may be economic influences on their career; 8: Historical context shapes who Gen Xers are as adults; 9: Baby Boomer influences contribute to job dissatisfaction; 10: Extrinsic motivators; 11: Intrinsic motivators; 12: Job satisfaction or dissatisfaction can carry over to life. The global themes are further comprised of organizing and basic themes to provide additional breadth and depth of understanding of this phenomenon. The study concludes by acknowledging that the voices of the Generation X participants have been heard through the compilation of their personal stories. It is noted that their stories and experiences were largely influenced by three primary factors which include recognition of the individuality of Gen Xers, lack of mutual exclusivity between generational cohorts, and the significance of context in understanding one's lived experience. Finally, drawing from the findings, recommendations are provide to inform research, theory and practice.
Keywords: job satisfaction; Baby Boomers; Millennials; hermeneutic phenomenology; Generation X